Design anthropological futures
1 online resource (304 pages).
Keywords: A major contribution to the field, this ground-breaking book explores design anthropology's focus on futures and future-making. Examining what design anthropology is and what it is becoming, the authors push the frontiers of the discipline and reveal both the challenges for and the potential of this rapidly growing transdisciplinary field.Divided into four sections - Ethnographies of the Possible, Interventionist Speculation, Collaborative Formation of Issues, and Engaging Things - the book develops readers' understanding of the central theoretical and methodological aspects of future knowledge production in design anthropology. Bringing together renowned scholars such as George Marcus and Alison Clarke with young experimental design anthropologists from countries such as Denmark, Sweden, Austria, Brazil, the UK, and the United States, the sixteen chapters offer an unparalleled breadth of theoretical reflections and rich empirical case studies.Written by those at the forefront of the field, Design Anthropological Futures is destined to become a defining text for this growing discipline. A unique resource for students, scholars, and practitioners in design anthropology, design, architecture, material culture studies, and related fields.